2020
DOI: 10.1109/tuffc.2019.2943646
|View full text |Cite
|
Sign up to set email alerts
|

3-D Super-Resolution Ultrasound Imaging With a 2-D Sparse Array

Abstract: High frame rate 3-D ultrasound imaging technology combined with super-resolution processing method can visualize 3-D microvascular structures by overcoming the diffraction limited resolution in every spatial direction. However, 3-D superresolution ultrasound imaging using a full 2-D array requires a system with large number of independent channels, the design of which might be impractical due to the high cost, complexity, and volume of data produced.In this study, a 2-D sparse array was designed and fabricated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 68 publications
0
57
0
Order By: Relevance
“…The major advantage is that the volume is focused in all three directions including the elevation direction, which yields a resolution of (1.17λ × 2.12λ × 0.63λ ) at a depth of 15 mm. This was attained for a modest 62 elements, which both reduces the amount of data from the probe by a factor of 8 compared to previous 3-D SRI [13] as well as the beamforming time for a probe with 4 times the area of a 1024 elements 2-D matrix probe. Points outside in y-z plane Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The major advantage is that the volume is focused in all three directions including the elevation direction, which yields a resolution of (1.17λ × 2.12λ × 0.63λ ) at a depth of 15 mm. This was attained for a modest 62 elements, which both reduces the amount of data from the probe by a factor of 8 compared to previous 3-D SRI [13] as well as the beamforming time for a probe with 4 times the area of a 1024 elements 2-D matrix probe. Points outside in y-z plane Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In the future, with the development of fast 3D ultrasound imaging technology using a 2D transducer matrix 32 , vUS can be easily adopted for 3D velocimetry of the whole rodent brain. In addition, in combination with oxygenation measurements using multispectral photoacoustic tomography (mPAT) and given the blood flow (velocity) measured by vUS, the direct biomarker indicating neuron activity, i.e., the metabolic rate of oxygen, can be readily measured, which will greatly facilitate neuroscience research.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, this apparatus was able to reconstruct entire super-resolved volumes of the rat brain, alleviating the previously described drawbacks with 3-D tracking and motion correction. Harput et al (2019b) reduced the number of connected channels by implementing super-resolution on a 2-D sparse array. 3-D super-resolution could even be performed with a clinical scanner as described by Christensen-Jeffries et al (2018).…”
Section: Three Dimensionsmentioning
confidence: 99%
“…In the past decade it has been well reported that the vaporization of such phase-change nanodroplets into microbubbles can be controlled by acoustic pressure (Sheeran et al 2012). This phase transition also depends on nanodroplet characteristics (e.g., size distribution and boiling point of the gas) and external factors (e.g., microvessel confinement [Lin et al 2018] and attachment to cells [Zhang et al 2019b]).…”
Section: Super-resolution Ultrasound Using Phase-shift Agentsmentioning
confidence: 99%
See 1 more Smart Citation